A New Golden Age in International Higher Education: Challenges and Successes during the Pandemic and Beyond (Comparative & International Education Series, 2021)
This introductory chapter responds to the growing need for new insights and perspectives to improve global student mobility policy and practice in the era of COVID-19. Specifically, this chapter gives an overview of the book and draws an outline of the impacts for global mobility in the field of comparative and international higher education. We highlight international student trends and the need for developing programs, policies, and systems that align with national needs, institutional priorities, and student well-being for global learning.